2018
DOI: 10.31788/rjc.2018.1145048
|View full text |Cite
|
Sign up to set email alerts
|

A NEW EFFECTIVE ADSORBENT DERIVED FROM THE BARKS OF Ziziphus mauritiana PLANT FOR THE REMOVAL OF CHROMATE FROM POLLUTED WATER

Abstract: An adsorbent prepared from Ziziphus mauritiana barks powder (ZMBP) is found to adsorb Chromate ions from water. The extractions conditions for the maximum removal of Chromate ions from water are optimized. 94.0% of Chromate is removed from water having 20 mg/L of Chromate ions at pH = 2, agitation time: 90 min, adsorbent dosage: 0.5 g/500mL, rpm: 250 and temp.: 30°C ± 1°C. The adsorption capacity is 18.8 mg/g. Co-ions are less interfered. Spent adsorbents can be regenerated and reused up to three cycles. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Our research group is investigating these aspects of purification of polluted water and found some successful methods for the extraction of F -, Pb 2+ , Cr (VI), NO2 -, NH3, PO4 3and Dyes. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] While we are investigating different bio-materials of the different plant as adsorbents for the extraction of different pollutive ions, stems of Cassia Occidentalis plant are noted to have good adsorption nature towards Al (III) ions. Hence, in this work, an adsorbent derived from Cassia Occidentalis plant stems is investigated for its adsorption nature towards Al (III) ions by optimizing the various conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group is investigating these aspects of purification of polluted water and found some successful methods for the extraction of F -, Pb 2+ , Cr (VI), NO2 -, NH3, PO4 3and Dyes. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] While we are investigating different bio-materials of the different plant as adsorbents for the extraction of different pollutive ions, stems of Cassia Occidentalis plant are noted to have good adsorption nature towards Al (III) ions. Hence, in this work, an adsorbent derived from Cassia Occidentalis plant stems is investigated for its adsorption nature towards Al (III) ions by optimizing the various conditions.…”
Section: Introductionmentioning
confidence: 99%